PERSEPSI MASYARAKAT PESISIR TERHADAP PEMBANGUNAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN SIAK - Riyadi Mustofa (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract : This study was intended to determine the perceptions of coastal communities on the development of palm oil plantations in Siak Regency in improving the welfare of farmers. While the purpose of this study is to analyze how much the positive impact of the development of palm oil plantations on the welfare of farmers and surrounding communities. The population in this study were self-help palm oil farmers who carried out opalm oil cultivation on coastal land. Samples were taken from communities in selected research sub-districts. Sampling was carried out by purposive sampling so that each selected region contained a sample representing self-supporting smallholder palm oil plantations. Data analysed using descriptive analysis with frequency distribution table. The results of the study show that the development of plantations can prosper the community for farmers and the surrounding community. For garden owners, ushatani oil palm is a long-term investment destination that is considered the most profitable.For communities around plantations or not garden owners, the existence of oil palm plantations can open employment opportunities. Keywords: Palm Oil, Coastal Land, Community Perception